Time interval between surgery and start of adjuvant radiotherapy in patients with soft tissue sarcoma: A retrospective analysis of 1131 cases from the French Sarcoma Group. Issue 1 (July 2016) - Fourquet, Jacques; Sunyach, Marie-Pierre; Vilotte, Florent; Le Péchoux, Cécile; Ranchère-Vince, Dominique; Bonvalot, Sylvie; Coindre, Jean-Michel; Terrier, Philippe; Meeus, Pierre; Helfre, Sylvie; Martin, Etienne; Vogin, Guillaume; et al.
Abstract: Purpose: The aim of this study was to evaluate the impact of the time interval (TI) between surgery and adjuvant radiotherapy (RT) in soft tissue sarcoma (STS). Methods and materials: Data from 1131 patients treated between 1990 and 2014 were retrospectively reviewed. Inclusion criteria were: limb or superficial trunk wall STS (R0 or R1 resection) and adjuvant RT. The impact of TI on 10-year local relapse-free survival (LRFS) and 10-year overall survival (OS) was analyzed using a Log-rank test and then Cox Model. Results: The median TI was 82 days (range, 18–346). With a median follow-up of 235 months (range, 2–296 months), the 10-year LRFS was 57.5% (±2%) and the 10-year OS was 64.2% (±2%). With a TI of 19–39 days, 40–79 days, 80–119 days, and ⩾120 days, 10-year LRFSs were 65.3%, 55.5%, 56.9% and 61.2% ( p = 0.465), and 10-year OSs were 72.8%, 60.7%, 66.4% and 62.1% ( p = 0.347), respectively. After adjustment for the factors significantly ( p ⩽ 0.05) associated with LRFS and OS, TI did not alter LRFS ( p = 0.182) either OS ( p = 0.335). Conclusions: In this retrospective STS database study, the TI between surgery and start of adjuvant RT did not seem to affect outcomes.